Establishing surrogate kidney endpoints for lupus nephritis clinical trials: development and validation of a novel approach to predict future kidney outcomes - Mackay, M; Dall’Era, M; Fishbein, J; Kalunian, K; Lesser, M; Guerrero, J; Levy, DM; Silverman, E; Petri, M; Arriens, C; Lewis, EJ; Korbet, SM; et al. (Wiley, 2019)
Objective: Endpoints currently used in lupus nephritis (LN) clinical trials lack uniformity and questionably reflect long‐term kidney survival. The objective of this investigation was to identify short‐term endpoints that predict long‐term kidney outcomes for use in clinical trials. Methods: A database of 944 LN patients was assembled from 3 clinical trials and 12 longitudinal cohorts. Variables from the first 12 months of treatment after diagnosis of active LN (prediction period) were assessed as potential predictors of long‐term outcomes in a 36 month follow‐up period. The long‐term outcomes examined were new or progressive chronic kidney disease (CKD), severe kidney injury (SKI), and the need for permanent renal replacement therapy (RRT). Hazard Index Tools (HITs) to predict risk for each outcome were derived using multivariable analysis with Cox proportional hazards regression. Results: Among 550 eligible subjects 54 CKD, 55 SKI and 22 RRT events occurred. Variables in the final CKD HIT were prediction period CKD status, 12‐month proteinuria and12‐month serum creatinine (SCr). The SKI HIT included prediction period CKD status, ISN Class, 12‐month proteinuria, 12‐month SCr, race and an interaction between ISN Class and 12‐month proteinuria. The RRT HIT included age at diagnosis, 12‐month proteinuria and 12‐month SCr. Each HIT validated well internally (c‐indices 0.84‐0.92) and in an independent LN cohort (c‐indices 0.83‐0.92). Conclusion: HITs, derived from short‐term kidney responses to treatment correlate with long‐term kidney outcomes, and now must be validated as surrogate endpoints for LN clinical trials.